Antimildew Treatment and Control Effect of Citral on Bamboo - Jingjing Zhang; Chungui Du; Rui Peng; Ailian Hu; Qi Li; Chunlin Liu; Yingying Shan; Shiqin Chen; Wenxiu Yin (International Journal of Polymer Science)
Presently, chemical agents remain the main antimildew agents for bamboo, which has a certain negative impact on the environment and human health. Therefore, it is urgent to develop new environment-friendly antimildew agents for bamboo. Here, citral, an environment-friendly natural antibacterial agent, was used as an antimildew agent for bamboo. The orthogonal test was used to explore the effects of citral concentration, impregnation pressure, and pressurization time on the drug loading capacity of treated bamboo strips. The effect of antimildew-treated bamboo strips on bamboo mold was also discussed. Furthermore, the Fourier transform infrared spectroscopy and ultraviolet spectrophotometer were used to investigate the distribution of citral in bamboo strips. Results showed that the optimum technological parameters of citral mildew-proof treatment of bamboo were as follows: citral concentration: 0.795 mg/ml, impregnation pressure: 0.3 MPa, and pressurization time: 90 min. Also, citral was easy to volatilize, which decreased the citral content of bamboo strips after vacuum drying and showed the trend of a lower surface layer and a higher inner layer. The concentration of citral therefore had a significant effect on the drug loading of the antimildew-treated bamboo strips. Thus, it was difficult to achieve effective prevention and control of bamboo mold when bamboo strips were impregnated with a lower concentration of citral solution. When the concentration of citral reached 200 mg/ml, the prevention and antimold efficiency of antimildew bamboo strips reached over 100%. This study will provide references for the development and application of environment-friendly natural antibacterial agents in the field of bamboo mildew prevention.